Monomia calla, a new species of swimming crab (Decapoda, Portunidae) from Madagascar and the Philippines - Koch, Milan; Nguyen, Thanh Son; Ďuriš, Zdeněk (Zootaxa, 2015)
A new species of portunid crab (Brachyura: Portunidae) from southern Madagascar and central Philippines is described. Monomia calla sp. nov. is most similar in morphology to M. lecromi (Moosa, 1996) from the Chesterfield Islands in the southwestern Pacific Ocean, and M. rubromarginata (Lanchester, 1900) from the South China Sea, Singapore, Malay Archipelago and the northern half of Australia. The new species can be easily distinguished from all congeners by the distinctive morphology of the male first gonopod. The number of species of the Indo-West Pacific genus Monomia now stands at 12.